The Conflict Analysis of Balinese Women on Equality in Work, Family and Social Life - I Made Yuda Suryawan; Ni Luh Tut Tri Ratnawati; Jonathan Jacob Paul Latupeirissa (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
Currently, women play an active role in operational implementation. Therefore, women are also required to spend most of their time working. Of course this will create a dual role conflict for women as a housewife and also as a person who works. Apart from that, social life also has its own demands in daily life. This research was conducted at the Secretariat Office of the Traditional Village of Legian. This office is located at Jl. Legian No. 447, Kuta District, Badung Regency, Bali Province. The method used in this research is a qualitative research method with case studies. The informants in this study were the Head of the Traditional Village of Legian, the Head of Governmental Affairs for the Traditional Village of Legian and 8 Balinese women workers who were married and had children. Data analysis conducted in this study was to analyze the results of observations, interviews, and documentation obtained from the study. The results showed several things that could lead to multiple role conflicts experienced by female employees, including the lack of or even no time for family which ultimately resulted in neglect of household chores, neglect of children and even husbands; the absence of time to socialize which results in women not socializing with neighbours and can make relations with neighbours not harmonious; the use of holidays for work so that when the holidays that should be used and spent with the family are instead used for work which makes all preparations for the holidays not optimal; problems in work that often carry over to the house; problems in the family, and complaints from family members regarding the work undertaken by female employees and the absence of support from the closest people, either husband, parents-in-law or parents.